Accommodating Hindu Religious Events for the Buddhist Community in Banyuasin Regency, Palembang - Komang Sutawan; Ida Ayu Komang Arniati; Burmansah Burmansah (Sahabat Publikasi, 2026)
This research is motivated the phenomenon of Buddhist involvement in ritual and social practices derived from the Hindu religious tradition in Banyuasin Regency, which has not been studied in depth from a scientific perspective. The research focuses on how interfaith accommodation is interpreted and maintained within a multicultural society. The concept of “accommodation of Hindu religious events” refers to socio-religious adaptation, where Buddhists participate in Hindu-based activities without losing their religious identity. This research aims to analyze the causes, forms, and meanings of such accommodation practices. Using a qualitative approach with a religious anthropological perspective, data were collected through observation, in-depth interviews, and documentation involving religious leaders and local communities.. The results of the study show that accommodation practices are not solely driven by a single factor, but are social constructions formed through historical interactions, kinship closeness, geographical conditions, and internalization of the values of tolerance and harmony. In practice, this accommodation manifests itself in the form of active participation in marriage ceremonies, deaths, as well as religious and traditional celebrations. Analytically, this practice reflects a flexible negotiation of religious identity, in which Hindu religious symbols and events are reinterpreted as part of a shared social tradition, rather than merely as doctrinal expressions. Furthermore, the meaning of the accommodation does not only stop at the aspect of tolerance, but develops into an effective social integration mechanism in maintaining community cohesion. This practice also has implications for strengthening social relations, the stability of religious life, and the sustainability of local culture.